Cosmogonic Image of Dragon-Ouroboros in Artistic Perception of Russian Far Eastern Emigration Writer B. Yulskiy - E. O. Kirillova (Научный диалог, 2018)
The article is devoted to the study of literature of Russian Far Eastern emigration on the example of the works by Boris Mikhaylovich Yulskiy (1911-1950?), whose life and fate were linked with the Far Eastern emigration. The relevance of the study is determined by the interest of scientists to the ancient and completely unlike Chinese culture. In 2012 in Vladivostok the only book by Yulskiy “Green Legion” was published. It is noted that the collection of stories is edition that includes the writer’s works collected on the pages of the Russian-language periodicals of China (mainly Harbin magazine “Rubezh”). It is stated that merit of Yulskiy became the work with regional material, that gave his prose “Far Eastern” flavour. The object of study in the present article is the work of art “The Way of the Dragon.” The novelty of the article is seen in the fact that the image of the dragon from this work has not been investigated before. On the example of the Chinese mythological image of the dragon-Ouroboros, the category of “Dao,” as well as the motives of non-doing, contemplation, opium smoking, hermit the reflection of the perception of the elements of Chinese culture in the work of the Russian writer is revealed. It is concluded that Yulskiy who belonged to the “younger” generation of Harbin emigrants and had being living in Harbin with parents from his boyhood, fully embraced the surrounding Chinese culture and rather originally reflected it in his “Russian” stories.